Chemical composition and bioactivity of Boswellia serrata Roxb. essential oil in relation to geographical variation. (4th July 2017) - Gupta, M.; Rout, P. K.; Misra, L. N.; Gupta, P.; Singh, N.; Darokar, M. P.; Saikia, D.; Singh, S. C.; Bhakuni, R. S.
Abstract: Oleo–gum–resin of Boswellia serrata Roxb. (Burseraceae) was collected from Shivpuri forest situated in northwestern district of Madhya Pradesh, India. The commercial samples were purchased from Mandsaur and Neemuch districts (the major herbal markets of Madhya Pradesh) for comparative study of their essential oils. The average essential oil contents in the commercial Neemuch samples (11.1%) were much better as compared to the wild collection from Shivpuri (6.1%) as well as commercial collection from Mandsaur (6.9%). The commercial samples contained higher percentage of monoterpene hydrocarbons (81.9–88.1%) including α-thujene (61.4–69.8%) as the major compound. The wild habitat contained higher percentage of oxygenated monoterpenoids/benzenoids (15.7%) and sesquiterpenes (19.2%) including α-terpineol (7.8%), terpinyl isobutyrate (5.1%), and eudesmol (11.5%). Further, the antimicrobial activities of these collections showed remarkable variation among the essential oils. On the other hand, wild habitat contained improved percentage of semi-polar compounds (34.9%) which might be responsible for enhanced antibacterial activity. Similarly, the winter collection from Neemuch (BS-N2) showed significant antioxidant activity, whereas the wild habitat did not show any antioxidant activity. The higher percentage of monoterpene hydrocarbons in commercial samples, especially δ-3-carene, α-pinene, and α-thujene, might be responsible for enhanced antifungal and antioxidant activities. The Pearson correlation values justify the bioactivity relationship of the major compounds with different microbial strains. It also justified the interaction among the major individual compounds.